The effective collaboration as a procedural political strategy against crime in Peru - Quiroz Salazar, Willian F. (2008)
The effective collaboration in our country consists in sharing relevant information of a criminal  event where  the  informant  has  taken  part  like author, coauthor or contributor on the felony. The 472º article of the Criminal Procedural Code of 2004 demands that the informant has voluntarily declared his criminal activities, seeking to fulfill a dual function; on the one hand, to demand as a requirement that the future informant leaves his illicit activities; and on the other hand, the role of general prevention. Finally, the effective collaboration must be seen like a procedural strategy to face criminal impunity and for the discovery of criminal organizations.